U.S. Intelligence and the Soviet Strategic Threat : Updated Edition - Freedman, Lawrence (Book collections on Project MUSE., 1986)
The author examines in detail the organization of the U.S. intelligence community, its attempts to monitor and predict the development of Soviet forces from the early days of the cold war, and how these attempts affected American policy and weapons production.Originally published in 1987.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.